2018
DOI: 10.7554/elife.40262
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin-mediated social enrichment promotes longer telomeres and novelty seeking

Abstract: The quality of social relationships is a powerful determinant of lifetime health. Here, we explored the impact of social experiences on circulating oxytocin (OT) concentration, telomere length (TL), and novelty-seeking behaviour in male and female rats. Prolonged social housing raised circulating OT levels in both sexes while elongating TL only in females. Novelty-seeking behaviour in females was more responsive to social housing and increased OT levels than males. The OT antagonist (OT ANT) L-366,509 blocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 93 publications
3
26
0
Order By: Relevance
“…This research has also shown that females are generally more responsive to social aspects of EE than males (Faraji et al, 2018a;Faraji et al, 2018b;Faraji et al, 2017b). These benefits are associated with oxytocin-mediated telomere elongation, a biological marker of longevity, indicating improved ageing trajectories (Faraji et al, 2018a). This work has helped elucidate the biological underpinnings of social isolation and support the critical role of social enrichment as a treatment option to reverse adverse consequences of stress and enhance stress resiliency.…”
Section: Mitigation Strategies and Interventionsmentioning
confidence: 69%
See 2 more Smart Citations
“…This research has also shown that females are generally more responsive to social aspects of EE than males (Faraji et al, 2018a;Faraji et al, 2018b;Faraji et al, 2017b). These benefits are associated with oxytocin-mediated telomere elongation, a biological marker of longevity, indicating improved ageing trajectories (Faraji et al, 2018a). This work has helped elucidate the biological underpinnings of social isolation and support the critical role of social enrichment as a treatment option to reverse adverse consequences of stress and enhance stress resiliency.…”
Section: Mitigation Strategies and Interventionsmentioning
confidence: 69%
“…Major aspects of sex differences in social interaction may be explained by the response to oxytocin (OT), an evolutionarily conserved neuropeptide which is critically involved in social bonding, cognition and improved coping with stress (Caldwell, 2018;Grewen and Light, 2011). For instance, females appear more vulnerable than males to genetic and behavioural changes when the secretion of endogenous oxytocin in response to social life is interrupted (Faraji et al, 2018a). Also, oxytocin may facilitate various forms of prosocial behaviours, building trust and enhancing sociality in humans and non-human animals (Holt-Lunstad et al, 2015;Kreuder et al, 2020;Ma et al, 2016;Mottolese et al, 2014;Olff et al, 2013;Rimmele et al, 2009;Theodoridou et al, 2009), an effect that would presumably enhance social engagement (Figure 2).…”
Section: Social Interaction: the Precursor Of Psychobiological Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…We validated 76 genes showing consistent increased accessibility in their enhancers and promoters (p-adj<0.01, Figure S1E). Additionally, SONO-seq showed differential accessibility on pathways that are important in neuronal function such as MAPK and JNK (Coffey, 2014), neural maturation BMP (Bond et al, 2012), synaptic plasticity PI3K-Akt (Tan et al, 2017), cellular aging prevention and telomere protective role of oxytocin (Faraji et al, 2018;Stevenson et al, 2019), and neurotransmission function by GPCR (Betke et al, 2012) (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Rats are social animals, and previous studies have shown that their physical and mental abilities are better when they live in socially enriched housing ( Leggio et al, 2005 ; van Praag et al, 2000 ). Now, in eLife, Reza Moeeini of the Avicenna Institute of Neuroscience, Gerlinde Metz of the University of Lethbridge and co-workers – including Jamshid Faraji, who is also at Golestan University of Medical Sciences – report a molecular mechanism that enables social interactions to have beneficial effects on the cells of rats ( Faraji et al, 2018 ).…”
mentioning
confidence: 99%